2007
DOI: 10.1152/physiolgenomics.00188.2007
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition-induced ketosis alters metabolic and signaling gene networks in liver of periparturient dairy cows

Abstract: Dairy cows are highly susceptible after parturition to developing liver lipidosis and ketosis, which are costly diseases to farmers. A bovine microarray platform consisting of 13,257-annotated oligonucleotides was used to study hepatic gene networks underlying nutrition-induced ketosis. On day 5 postpartum, 14 Holstein cows were randomly assigned to ketosis-induction (n = 7) or control (n = 7) groups. Cows in the ketosis-induction group were fed at 50% of day 4 intake until they developed signs of clinical ket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
304
3
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(370 citation statements)
references
References 58 publications
(68 reference statements)
32
304
3
8
Order By: Relevance
“…It is reported that intake restriction resulted in a significant decrease of blood glucose concentration in cattle [12,13], in diary cows [14], deer [4] and horse [15]. Furthermore, previous studies also showed that reduced feed consumption resulted in metabolic disorder in cattle, sheep, deer, ilama, and rats [3,4,5,6], disturbance of acid-base balance of body fluids [7], and hepatic lipidosis [8]. Furthermore, the ADG of of the Kacang goats during the refeeding period was 0.11±0.05 kg/day and showed that the body weight of the Kacang goats increased significantly.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is reported that intake restriction resulted in a significant decrease of blood glucose concentration in cattle [12,13], in diary cows [14], deer [4] and horse [15]. Furthermore, previous studies also showed that reduced feed consumption resulted in metabolic disorder in cattle, sheep, deer, ilama, and rats [3,4,5,6], disturbance of acid-base balance of body fluids [7], and hepatic lipidosis [8]. Furthermore, the ADG of of the Kacang goats during the refeeding period was 0.11±0.05 kg/day and showed that the body weight of the Kacang goats increased significantly.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies showed that reduced feed or protein consumption resulted in metabolic disorder in cattle, sheep, deer, ilama, and rats indicated by alteration of some blood chemistry profiles, such as glucose, lipid and protein [3,4,5,6] and in disturbance of acid-base balance of body fluids [7]. Moreover, study in cattle revealed that feed restriction might lead to the occurrence of hepatic lipidosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ketosis is a polyetiological disease, often complicated by other diseases. Impaired functions of liver, pancreatic gland, other organs are often observed in sick animals (Steen, 2001;Stojević et al, 2005;Loor et al, 2007;Gonzalez & Rosendo, 2013) which may complicate diagnostics and further treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, because restricted-energy fed cows did not experience fatty liver relative to energy-overfed cows (Loor et al, 2006) it is apparent that different signals are capable of triggering the same metabolic adaptations in liver, for example, cows with severe nutrition-induced ketosis early postpartum also upregulate fatty acid catabolism pathways in liver (Loor et al, 2007). A novel observation in cows fed restrictedenergy prepartum was the enrichment of antigen processing and presentation pathways enriched in a cluster of clearly upregulated genes.…”
Section: Linking Cattle Genome To Ruminant Metabolismmentioning
confidence: 99%
“…An initial characterization of liver transcriptional adaptations to saturated v. polyunsaturated fatty acid supplementation at 210, 1 and ,14 days relative to parturition with a bovine microarray (Loor et al, 2007) has revealed some unique adaptations (Khan et al, 2010). Treatment diets were fed from 21 days before expected date of parturition until ,10 days after parturition (Ballou et al, 2009).…”
Section: Linking Cattle Genome To Ruminant Metabolismmentioning
confidence: 99%